IMPLEMENTASI KEBIJAKAN ADAPTASI KEBIASAAN BARU DI MASA PANDEMI COVID-19 (Studi Pada Masyarakat Pelaku UMKM di Sekitar Lingkungan Kampus IAI Darussalam Kelurahan Tanjung Rema Martapura) - Dairobi Dairobi; Lola Malihah; M Yulian Ma’mun; Bahriah Bahriah (Journal MISSY (Management and Business Strategy), 2021)
The Indonesian government policies in implementing "adaptation of new habits" during the Covid-19 pandemic are received various responses from the public. Some people are very supportive of the implementation because they are aware of the benefits and know the dangers of Covid-19. Furthermore, the others are still ignorant and do not respond well to the government's policy for various reasons. Among them are the economic reason and a lack of understanding of the Covid-19 risks and their implications for human health. The government also begin vaccination across the country to prevent the spread of the virus. This study uses a quantitative-descriptive method. It aims to determine the implementation of the "adaptation of new habits" in the community of the MSME businesspeople around the Darussalam Islamic Institute Martapura campus during the Covid-19 pandemic period. This study concludes that most of them obeyed the new Covid-19 health policies implemented by the government because most of them understand the dangers of Covid-19 transmission.